Application of Pop Up Method in Improving Student Learning Achievement in Indonesian Language Learning Illustration Picture Material at MI Tarbiyatul Hidayah Boteng Menganti Gresik - Suciati, Wahyu (MANDAILING GLOBAL EDUKASIA, 2025)
This study aims to examine the application of the Pop Up method in learning Indonesian language on illustration material at MI Tarbiyatul Hidayah Boteng Menganti Gresik. The Pop Up method was chosen because it can create a more interesting and interactive learning atmosphere for students, and make it easier for them to understand the concept of illustration. This study uses a qualitative approach with a descriptive method to observe the implementation of learning, and analyze the results achieved by students after the application of the method. In its implementation, the Pop Up method allows students to draw illustrations based on the story text given, and fosters their creativity and imagination in interpreting stories through pictures. The results of the study showed that the application of the Pop Up method can increase students' interest and involvement in learning Indonesian. Students are more enthusiastic and active in drawing illustrations, and are able to connect images with the contents of the text in more depth. In addition, students can also understand the message contained in the story better through drawing activities. Based on these results, it can be concluded that the Pop Up method is effective in improving students' understanding of illustration material, and can be used as an alternative in developing creative and enjoyable learning at MI Tarbiyatul Hidayah Boteng Menganti Gresik